Hyperglycemia induces inflammatory response of human macrophages to CD163-mediated scavenging of hemoglobin-haptoglobin complexes - Matuschik, Laura; Riabov, Vladimir; Schmuttermaier, Christina; Sevastyanova, Tatyana; Weiß, Christel; Klüter, Harald; Kzhyshkowska, Julia (International journal of molecular sciences, 2022)
Hyperglycemia, a hallmark of diabetes, can induce inflammatory programming of macrophages. The macrophage scavenger receptor CD163 internalizes and degrades hemoglobin-haptoglobin (Hb-Hp) complexes built due to intravascular hemolysis. Clinical studies have demonstrated a correlation between impaired scavenging of Hb-Hp complexes via CD163 and diabetic vascular complications. Our aim was to identify whether hyperglycemia is able to amplify inflammation via Hb-Hp complex interactions with the immune system. M(IFNγ), M(IL-4), and control M0 macrophages were differentiated out of primary human monocytes in normo- (5 mM) and hyperglycemic (25 mM) conditions. CD163 gene expression was decreased 5.53 times in M(IFNγ) with a further decrease of 1.99 times in hyperglycemia. Hyperglycemia suppressed CD163 surface expression in M(IFNγ) (1.43 times). Flow cytometry demonstrated no impairment of Hb-Hp uptake in hyperglycemia. However, hyperglycemia induced an inflammatory response of M(IFNγ) to Hb-Hp1-1 and Hb-Hp2-2 uptake with different dynamics. Hb-Hp1-1 uptake stimulated IL-6 release (3.03 times) after 6 h but suppressed secretion (5.78 times) after 24 h. Contrarily, Hb-Hp2-2 uptake did not affect IL-6 release after 6h but increased secretion after 24 h (3.06 times). Our data show that hyperglycemia induces an inflammatory response of innate immune cells to Hb-Hp1-1 and Hb-Hp2-2 uptake, converting the silent Hb-Hp complex clearance that prevents vascular damage into an inflammatory process, hereby increasing the susceptibility of diabetic patients to vascular complications.